Developing a `letter to my younger self` to learn from the experiences of expert coaches - Szedlak, C.; Smith, M. J.; Callary, B. (Qualitative Research in Sport, Exercise and Health, 2021)
This study is focused on how novice sport science practitioners can learn from the hindsight of more experienced practitioners, and how such information can be effectively disseminated. Initially, 13 expert, elite-level, strength and conditioning coaches wrote a reflective letter to their `younger selves` offering advice in terms of things they had learnt throughout their coaching career. Thematically analysed, five themes were generated: willingness to learn and develop, appreciating the contribution of others, understanding and behaving in line with values, embracing uncertainty and difficult challenges and creating and maintaining a work-life balance. Framed around these themes, the authors employed creative writing techniques to develop a composite letter with quotes extracted that best represented each theme, and woven together to create a final, coherent letter. To systematically examine the efficacy of using such a letter as a scaffolding learning strategy to advise early career practitioners, the letter was presented to 25 participants who were all on MSc Strength and Conditioning courses. Five focus groups were conducted to examine the participants` perceptions of the letter. Thematically analysed, the findings highlight that the letter resonated with them and encouraged reflection in a number of specific ways (e.g. challenged their current approach to their coaching role, developed confidence to deal with challenges). We propose that the composite letter can be used as a pedagogic tool to stimulate reflection for new practitioners concerning their development, and offer motivation (to work hard in their own development) in the early stages of their career.